Aflatoxinas B1, B2, G1 e G2, fumonisina B1 e zearalenona em fubá: validação de método por cromatografia líquida acoplada a espectrometria de massas e ocorrência de contaminação - Fabiano Narciso Paschoal (2015)
Corn is the main product of world agriculture, and Brazil is the third largest producer. This is an extremely important product in the nutritional point of view. Although most of the grain produced in Brazil have destined for animal feed, which is a global trend, the cornmeal occupies a prominent position among the maize products for human consumption. Food contamination with mycotoxins is an important topic in food security, and the corn stands out as a product having the highest rates and varieties of contamination. Official methods described for the determination of mycotoxins in foods and feeds include a single measurand or a single group of measurands, using chromatographic techniques and immunoassays, and laborious extraction and clean-up steps. However, there is a trend to replace classical procedures by modern analytical techniques. In this context, ultra performance liquid chromatography coupled to tandem mass spectrometry allows the extension of the analytical scopes associated with a reduction of the time consuming, and solvent discard. In this paper, a rapid and single extraction method for simultaneous determination of aflatoxin B1 (AFB1), B2 (AFB2), G1 (AFG1), G2 (AFG2), fumonisin B1 (FB1) and zearalenone (ZEA) in cornmeal was validated and applied in an occurrence. Different extraction solutions were tested, with better performance for methanol:acetonitrile:water (60:20:20). Linearity was observed in the range from 0.25 to 1.50 for aflatoxins, from 20 to 120 for FB1 and from 7.00 to 42.00 ng/mL for ZEA. Significant matrix effects were demonstrated for all groups (p < 0.05). Average recoveries of 87.57, 93.18, 93.35, 94.20, 78.76 and 95.98 % were estimated to AFB1 AFB2, AFG1, AFG2, FB1 and ZEA, respectively, employing spiked samples. Maize certified reference material for FB1 was analyzed with score-z of 0.19. Maximum relative standard deviation under repeatability conditions and intermediate precision of 13.6 and 13.6 % for AFB1, AFB2, AFG1 and AFG2, of 3.7 and 6.3 % for FB1, and of 3.5 and 4.0 % for ZEA, respectively, were achieved. These results confirmed the accuracy of the method. In the occurrence study, for the 50 samples analyzed, 44 % had measurable levels of FB1 and ZEA was detected in 18 % of the samples. The validated method was considered fitness for the purpose of considering the determination of different groups of mycotoxins in cornmeal as part of the actions for the public health promotion.